New technologies in glass - Cutler, Vanessa (A & C Black, 2012)
An artist's perspective on new machinery and software for glass, the book describes technologies including engraving, 3D printing and rapid prototyping, with illustrations of works by contemporary artists. The book is a vital text for artists wishing to expand their repertoire and challenge the possibilities of glass.